Implementasi Peraturan Gubernur Bali No.46 Tahun 2020 Di Desa Batubulan - Ika Pramesti, Dewa Ayu Agung; Dharma Laksana, I Gusti Ngurah (Kertha Wicara : Journal Ilmu Hukum; Vol 10 No 1 (2020)DO - 10.24843/KW.2020.v10.i01.p06, 2020)
The purpose of writing this journal is to find out the results of the implementation of the Governor of Bali Regulation No.46 of 2020 concerning the Application of Discipline and Law Enforcement of Health Protocols as Efforts to Prevent and Control Corona Virus Disease 2019 in a New Era Life Order in Batubulan Village in improving discipline and law enforcement in order to prevent the spread of covid-19. In this paper, an empirical legal research method is used with interviews and data requested from the Batubulan village government. The results of this study show that the people of Batubulan village have been active and participatory in preventing the spread of the corona virus by complying with the calls and regulations submitted by the government. The Batubulan village government continues to socialize this regulation but does not implement administrative sanctions to its people who violate it, with the implementation of this regulation in Batubulan village patients confirmed positive for the corona virus experienced a very significant decrease even when this research was carried out there were no Batubulan villagers who were still exposed and no increase in the number of cases.   Key Words: Application, Bali Governor Regulation, Corona Virus